The Presence of the Prophet in Early Modern and Contemporary Islam Volume 2, Heirs of the Prophet: Authority and Power - Chih, Rachida; Reichmuth, Stefan; Jordan, David (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2022)
This second volume of the series The Presence of the Prophet, explores the growing importance of the figure of the Prophet Muhammad for questions of authority and power in many regions in early modern and modern times.; Readership: Scientific and general readership interested in Islam and Muslim culture and politics in different regional and historical contexts, Historical Anthropology, Sociology of Religion, Religion and Politics.